Elastic Hierarchies: Combining Treemaps and node-link diagrams - Shengdong Zhao; Michael J. McGuffin; Mark H. Chignell (InfoVis'05: Proceedings of the IEEE Symposium on Information Visualization, 2005)
We investigate the use of elastic hierarchies for representing trees, where a single graphical depiction uses a hybrid mixture, or "interleaving", of more basic forms at different nodes of the tree. In particular, we explore combinations of node link and treemap forms, to combine the space efficiency of treemaps with the structural clarity of node link diagrams. A taxonomy is developed to characterize the design space of such hybrid combinations. A software prototype is described, which we used to explore various techniques for visualizing, browsing and interacting with elastic hierarchies, such as side by side overview and detail views, highlighting and rubber banding across views, visualization of multiple foci, and smooth animations across transitions. The paper concludes with a discussion of the characteristics of elastic hierarchies and suggestions for research on their properties and uses.